Does the Pringle maneuver affect survival and recurrence following surgical resection for hepatocellular carcinoma? A western series of 441 patients. Issue 2 (29th October 2017) - Famularo, Simone; Giani, Alessandro; Di Sandro, Stefano; Sandini, Marta; Giacomoni, Alessandro; Pinotti, Enrico; Lauterio, Andrea; Gianotti, Luca; De Carlis, Luciano; Romano, Fabrizio
Abstract : Background: The impact of the Pringle maneuver (PM) on long‐term outcome after curative resection for hepatocellular carcinoma (HCC) is controversial, with eastern series reporting conflicting results. We aim to evaluate the impact of the PM in a western cohort. Methods: We retrospectively analyzed patients with HCC who underwent liver resection between January 2001 and August 2015. Patients were divided in two groups based the use of the PM during resection. Primary outcomes were overall survival (OS) and disease‐free survival (DFS). Results: A total of 441 patients were analyzed. Of these, 176 patients (39.9%) underwent PM. Median OS was 46.4 months (95%CI: 34.1‐58.7) for the PM group and 56.5 months (95%CI: 37.1‐75.9) for the no‐PM group ( P = 0.188), with a median DFS of 26.7 months (95%CI: 15.7‐37.7) and 24.9 months (95%CI: 18.1‐31.7), respectively ( P = 0.883). Conclusions: These results suggest that PM does not increase the risk of tumor recurrence or decrease long‐term survival.